PENGARUH STRUKTUR KEPEMILIKAN SAHAM TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN (CSR) (STUDI EMPIRIS PERUSAHAAN MANUFAKTUR YANG TERDAFATR DI BEI) - Arthur Reinaldo Tanihatu (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2016)
Corporate Social Responsibility is a corporate social responsibility to stakeholders, including theenvironment, customers, employees, communities, governments, suppliers, and even competitors. This studyexamines the effect of share ownership structure on the disclosure of corporate social responsibility. Shareownership structure is measured by institutional and managerial ownership. Researchers also included threeother variables are variables firm size, leverage and profitability as control variables. The results obtainedshowed the ownership of institutional and managerial ownership has no significant effect on the disclosure ofcorporate social responsibility. While the three variables control only the size of the company that proved tosignificantly affect the disclosure of corporate social responsibility, leverage and profitability has not beenproven.